Electromyographic studies on the "nage-waza" (throwing techniques) of judo - Ikai, M.; Asami, T.; Kaneko, M.; Sasa, T.; Matsumoto, Y. (Association for the Scientific Studies on Judo, Kodokan, 1963)
Many new training apparatuses have been introduced into the Weight Training Center of the Kodokan, recently, and it is expected that training in muscle strength will very soon begin in real earnest. Accordingly, before planning a course in muscle strength training, the determination of what groups of muscles are used during performance of a technique is of utmost importance. Also, of great importance from the point of view of analysis of movement is the determination of the mode of change in space and in time of the contraction phase and relaxation phase of the muscles during performance of the various forms of "Nage-waza" (throwing technique). The cinematographic and the overlapping exposure methods have usually been employed in the analysis of movement. However, these visual methods are not sufhcient as means of determining the mode of action of the muscles concerned. It is necessary to follow the locus of the movement, and to firmly grasp the mode of action of the various muscles of the body; and for these studies an electromyographical investigation becomes indispensable.